A motor neuron strategy to save time and energy in neurodegeneration: adaptive protein stoichiometry. Issue 5 (21st September 2018) - Zucchi, Elisabetta; Lu, Ching‐Hua; Cho, Yunju; Chang, Rakwoo; Adiutori, Rocco; Zubiri, Irene; Ceroni, Mauro; Cereda, Cristina; Pansarasa, Orietta; Greensmith, Linda; Malaspina, Andrea; Petzold, Axel
Abstract : This study describes a novel concept, adaptive protein stoichiometry, which provides neurons with an efficient strategy to slow neurodegeneration. The data supporting this conclusion come from protein concentrations measured in patients suffering from a rapid neurodegenerative condition, amyotrophic lateral sclerosis (synonymous motor neuron disease, Lou Gehrig disease). Extrapolation to a much boarder disease spectrum is conceivable as 'adaptive protein stoichiometry' is based on the fundamental principle of ATP and time requirements for transcription. The results of present data on the neurofilament triplet protein should be applicable to other heteropolymers and offer a new conceptional framework for developing antisense therapies. Abstract: Neurofilament proteins (Nf) are a biomarker of disease progression in amyotrophic lateral sclerosis (ALS). This study investigated whether there are major differences in expression from in vivo measurements of neurofilament isoforms, from the light chain, NfL (68 kDa), compared with larger proteins, the medium chain (NfM, 150 kDa) and the heavy (NfH, 200‐210 kDa) chains in ALS patients and healthy controls. New immunological methods were combined with Nf subunit stoichiometry calculations and Monte Carlo simulations of a coarse‐grained Nf brush model. Based on a physiological Nf subunit stoichiometry of 7 : 3 : 2 (NfL:NfM:NfH), we found an 'adaptive' Nf subunit stoichiometry of 24 : 2.4 : 1.6 in ALS. Adaptive Nf stoichiometry preserved NfL gyration radius in the Nf brush model. The energy and time requirements for Nf translation were 56 ± 27k ATP (5.6 h) in control subjects compared to 123 ± 102k (12.3 h) in ALS with 'adaptive' (24:2.4:1.6) Nf stoichiometry (not significant) and increased significantly to 355 ± 330k (35.5 h) with 'luxury' (7:3:2) Nf subunit stoichiometry ( p < 0.0001 for each comparison). Longitudinal disease progression‐related energy consumption was highest with a 'luxury' (7:3:2) Nf stoichiometry. Therefore, an energy and time‐saving option for motor neurons is to shift protein expression from larger to smaller (cheaper) subunits, at little or no costs on a protein structural level, to compensate for increased energy demands.